Voices: insulin and beyond - Roth, J; Ashcroft, FM; Wollheim, CB; Kieffer, TJ; Cherrington, AD; Bergman, RN; Taylor, R; Najjar, SM; Pedersen, O; Ellingsgaard, H; Holst, JJ; Nauck, MA; et al. (Cell Press, 2021)
Marking insulin’s centennial, we share stories of researchers and clinicians whose seminal work has advanced our understanding of insulin, islet biology, insulin resistance, and diabetes. The past century of pursuing the “hormone of hormones” and advancing diabetes therapies is replete with stories of collaboration, perseverance, and triumph.